RETRACTED: Physiology study for effecting of radon gas on some hormones of female rats - Algazali Sajad A.; Hassan Adhraa Baqir; Abojassim Ali Abid; Alkufi Abdulhussein A.; Abass Zainab Mohammed; Alsaialy Zaid A.; Chabok Zainab Mohamed (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001